Benchmarking in educational emergencies: Improving the quality of learning in the midst of a global crisis - Niken Lufi Anggini; Siti Aimah; Muhammad Imam Khaudli (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2025)
The global crisis has brought about fundamental changes in teaching methods, forcing the education system to adapt quickly and effectively. Many institutions face challenges such as unequal access to technology, inadequate infrastructure, and varying teacher readiness, which leads to disparities in the quality of learning. This study examines the application of benchmarking practices as a strategy to improve the quality of learning in the midst of crisis conditions. Through an in-depth analysis of SMK Negeri Darul Ulum Muncar, the study found that by adopting innovative teaching methods that have proven successful in other institutions, educational institutions can improve student engagement and academic achievement. The descriptive and qualitative approach applied allows for an in-depth understanding of the strategies used. The results show that the application of the best practices model adaptively not only maintains educational standards, but also encourages innovation in teaching methods. In addition, this study emphasizes the importance of building sustainable education system resilience to face future challenges. These findings are expected to provide guidance for stakeholders in implementing benchmarking as part of a sustainable improvement strategy, so that the quality of education is maintained in an uncertain crisis era.